A new method for scheduling divisible data on a heterogeneous two-levels hierarchical system - Shokripour, Amin; Othman, Mohamed; Ibrahim, Hamidah; Subramaniam, Shamala (Elsevier, 2011)
During the last decade, the use of parallel and distributed systems has become more common. In these systems, a huge chunk of data or computation is distributed among many systems in order to obtain better performance. Dividing data is one of the challenges in this type of systems. Divisible Load Theory (DLT) is proposed method for scheduling data distribution in parallel or distributed systems. In many researches carried out in this field, it was assumed that the used network topology is linear or one-level tree but that is not always true in real systems. In the large scale networks, hierarchical topology is usually used. In this article, we propose a new method which includes a closedform formula to schedule jobs in a heterogeneous distributed computing system in which its network topology is two-levels hierarchical system. The experiments show the calculated size for each processor is the best.